KEDUDUKAN ILMU DAN BELAJAR DALAM ISLAM - -, Mulyono (State Islamic Institute of Madura, 2009)
Islam is a religion that has great attention to science. Islam was emphasized his followers to continue their studies and learn and to remove it. In the Qur'an has explained that a noble person in the sight of Allah is only for two things; for his faith and because the height of their knowledge. Not because of the position or wealth. The first verse of God is revealed Surat al- Alaq, in the verse that God commands us to read and learn. God teaches us with Qalam often we mean with a pen. Therefore we can take the conclusions of science must be juxtaposed with faith. Can not be separated between the two. A cross between faith and science will produce an advanced civilization called The Islamic Civilization.